ANALISA NPL BANK UMUM KONVENSIONAL DILIHAT DARI CAR, LDR, ROA, DAN BOPO TERDAFTAR DI BEI - Wikan Isthika; Nita Sovia (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This research aims to analyse the impact of CAR, LDR, ROA and BOPO on NPL. The research object is Indonesian conventional banking listed on Indonesia Stock Exchange over the period 2019 to 2021. The total samples obtained 43 companies, and the data are financial reports and annual reports of Indonesian conventional banks. Analyse data is using descriptive test, classical assumption test, and multiple linear regression test. The results show that return on asset have significant impact on non-performing loans on Indonesian conventional banks, while capital adequacy ratio, loan to deposit ratio and operating expenses dividing by operating income have no significant impact on Indonesian conventional banks listed on Indonesia Stock Exchange.